SKELETON ANALYSIS OF Tursiops truncatus REGIO COSTAE AND SCAPULA STRANDED ON SENGGIGI BEACH, WEST LOMBOK - Qodri, Hasby faizul; Rahmawati, Septyana Eka; Riwu, Katty Hedriana Priscilia; Barmawi, Muhammad; Kholik (Jurnal Biosains Pascasarjana, 2024)
The dolphin (Tursiops truncatus) is the most studied and most common species of cetacean in captivity. In this study, the size results obtained were the ribs and scapula. The first measure is a difference from the proximal to the distal end between the literature and this study. the second and third sizes have long, short, and longer proximal to distal differences. The fourth, fifth and sixth sizes show that the bones of T.truncatus are smaller than those of the Numataphocoena yamashitai species and the seventh size shows that the differences between T.truncatus and the Numataphocoena yamashitai species are several short and long costae. For the scapula, the dimensions of the first and second bones are larger than the present study species T.truncatus and Numataphocoena yamashitai. The sizes of the three results from this study are almost the same as the species Numataphocoena yamashitai except for the species Prosqualodon marplesi, which is larger than this study and research in California. The fourth size, which is 49.0 mm from head to tuberculum, is larger than the species T.truncatus and Numataphocoena yamashitai studied. The fifth size, the diameter of the rib head of this research species is smaller than the species Numataphocoena yamashitai and Prosqualodon marplesi, both of which are smaller than T.truncatus, and some of these differences are caused by food, habitat and environmental conditions.